355. Invasive Pulmonary Aspergillosis (IPA) Complicating Respiratory Viral Infections in Patients With Hematological Malignancies. (26th November 2018) - Magira, Eleni; Chemaly, Roy F; Jiang, Ying; Kontoyiannis, Dimitrios P
Abstract: Background: Data regarding respiratory viral infections (RVIs) in patients with leukemia and/or stem cell transplantation (LSCT) and their predisposition to invasive pulmonary aspergillosis (IPA) are limited. To that end, we conducted a case–control study of post-RVI-IPA in LSCT patients. Methods: We analyzed all consecutive adult patients (2006–2016) with culture-documented IPA (EORTC/MSG criteria). Cases were patients with confirmed (either by nasal wash and/or BAL PCR and/or respiratory viral culture) RVIs [respiratory syncytial virus (RSV), Influenza A/B (INFA/B), or parainfluenza virus (PIV)] followed by IPA up to 5 weeks after. Controls were patients with IPA without evidence of RVIs. Results: We identified 54 cases (proven 1, probable 53), and 142 patients with IPA (proven 12, probable 130) as controls. The distribution of viruses were 34 PIV (52%), 18 INFA/B (27%), and 14 RSV (21%). The median days of post-RVIs-IPA infection was 8(−6–57) days. Among cases, the most common hematological malignancies were AML (34%) and CLL (26%). Most cases had prior allogeneic SCT (57%). Non- fumigatus Aspergillus species were the cause of IPA in 58% of cases. In univariate analysis, patients with post-RVs-IPA infection were more likely to be in complete or partial remission (43.9% vs. 22.3% P = 0.007), to have prior allogeneic SCT (57% vs. 31%, P = 0.0009) and an absolute lymphocyte count between 500 and 1, 000/mm 3 at RVI diagnosis (41% vs. 27%, P = 0.04). In addition, coinfections within 2 weeks after viral infection (58% vs. 18%, P = 0.0001), especially of the lower respiratory tract (37% vs. 18%, P = 0.004) were more common in patients with post-RVIs-IPA. RVIs-IPA patients were less likely to have an absolute neutrophil count <100 mm 3 at IPA diagnosis (17% vs. 37%, P = 0.005). Need for ICU post-RVIs-IPA disease (31% vs. 26% P = 0.5) and 42 days crude mortality (22% vs. 27%, P = 0.45) were no different between cases and controls. Conclusion: Post-RVIs-IPA occurs more frequently in patients with prior transplantation and is less associated with leukemia relapse and neutropenia. Although co-infections are common, this entity does not appear to be associated with worse outcome compared with IPA without preceding RVI. Disclosures: D. P. Kontoyiannis, Merck: Consultant, Research support and Speaker honorarium. Pfizer: Consultant, Research support. Astellas: Consultant, Research support and Speaker honorarium. Gilead: Speaker's Bureau, Speaker honorarium. F2G Inc.: Speaker's Bureau, Speaker honorarium. Cidara Inc.: Speaker's Bureau, Speaker honorarium. Jazz Pharmaceuticals: Speaker's Bureau, Speaker honorarium.